ANALISIS RANCANGAN APLIKASI PENJUALAN OBAT DI TOKO OBAT MANJUR - Cherissa Aeryn Djaya; Wasino; Teny Handhayani (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
In the era of rapid digitalization, all types of businesses, from small to large, need to enhance their competitiveness and provide added value to their customers. This research aims to develop a web-based application that can serve as a comprehensive solution for Manjur drug store in addressing challenges related to efficiency and data accuracy in medicine management. This research is intended to assist in the development of a web-based application that can be a comprehensive solution for the issues faced by Manjur drug store, which still conducts sales and data management manually that resulting in various risks such as errors in medication stock recording and a lack of store visibility. The application design are follows the SDLC (Software Development Life Cycle) methodology using the Waterfall model, employing the ASP.NET framework, C# programming language, HTML, CSS, Bootstrap, and SQL Server as the database. Therefore, it is expected that the application will improve the store’s operational efficiency, enhance data accuracy, simplify customer access, and strengthen Manjur drug store competitiveness in the market.